1986
DOI: 10.1177/002221948601900108
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study Of Learning Disabled Adults

Abstract: Personal and educational histories and test data of 33 learning disabled adults were collected and analyzed. Characteristics of this population are described, and an analysis of the test data is presented. It was found that many of the characteristics of learning disabled youngsters described in the literature persist into adulthood. Some significant sex differences in the Reasoning section of the Woodcock-Johnson Cognitive Ability Test and in Math Achievement are also reported. Issues related to understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 4 publications
3
21
0
1
Order By: Relevance
“…This male predominance in sample composition concurred with sex distribution in the samples of identified adults with LD reported by Buchanon and Wolf (1986) and Hoffmann et al (1987). The average age of the sample was 29.4 years (SZ) = 8.79).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This male predominance in sample composition concurred with sex distribution in the samples of identified adults with LD reported by Buchanon and Wolf (1986) and Hoffmann et al (1987). The average age of the sample was 29.4 years (SZ) = 8.79).…”
Section: Resultssupporting
confidence: 81%
“…The incidence and prevalence of LD in the adult population are difficult to determine for several reasons, including the absence of an operational definition of LD; insufficient diagnostic criteria; the lack of standardized assessment techniques; the tendency of adults with LD to compensate for or even "hide" their disabilities (Advisory Committee on Educational Opportunities for Adults, 1984); and limited self-awareness with respect to the underlying reasons for apparent functional problems (Buchanon & Wolf, 1986). Estimates have indicated that some type of learning disability exists in 15% of adults (Advisory Committee on Educational Opportunities for Adults, 1984) and that learning disabilities are disproportionately overrepresented in specific subgroups of the general population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With limited selfawareness and the poor self-concept that often accompanies learning disabilities (Hoffman et al, 1987), these individuals often experience significant difficulty setting and meeting meaningful goals and struggle to derive satisfaction from their lives (Buchanan & Wolf, 1986;Mangrum & Strichart, 1988). All too often, they find themselves struggling in the classroom (Mangrum & Strichart, 1988), underemployed, or otherwise inappropriately placed in the job market (Alley, Deshler, Schumaker, & Warner, 1983).…”
mentioning
confidence: 99%
“…Whereas accommodations are generally built into the system in high school, when the student enters the mainstream after graduation, the burden of self-advocacy greatly increases; decision making regarding when to disclose one's learning disability and when to request accommodations becomes a continuing issue (Buchanan & Wolf, 1986 uncomfortable about their abilities and disabilities may prefer to avoid participating in class rather than selfdisclose; in employment settings, employees with learning disabilities may feel reluctant to disclose their diagnosis for fear of experiencing social rejection or being fired; in social arenas, the young adult may be hesitant about when to divulge his or her learning disability to a new friend.…”
mentioning
confidence: 99%